The children’s story as an educational resource for the infant with ASD: a catalogue of children’s story - Pérez Marco, María; Fuster-Rico, Andrea; Gonzálvez, Carolina (Revista General de Información y Documentación, 2023)
Children's stories are a relevant educational resource for the comprehensive development of pupils, given the variety of educational implications on which they can have an impact. Students diagnosed with ASD present persistent difficulties in communication and social interaction, as well as in some executive functions. Based on a theoretical review, this study aims to offer a corpus of children's and young people's stories published in Spanish that can be used effectively for the educational intervention of students with ASD. After an exhaustive search and review of stories, a list of 40 children's books has been selected, which meet the 7 selection criteria previously established. These stories have been analysed according to descriptive and didactic variables (title, author, publisher, year, theme, summary, didactic relevance) and classified according to the area of intervention for which they are most conducive (social skills, communication, emotional education and/or behaviour). In conclusion, this study provides a reference source for teachers responsible for the intervention of students with ASD. It is also hoped that this work will contribute to highlighting the pedagogical value of storytelling as an educational and therapeutic resource.
Keywords: Autism Spectrum Disorder; Children’s story; Review; Catalogue; Special Education